2004
DOI: 10.1530/rep.1.00075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medium on the kinematics of frozen–thawed ram spermatozoa

Abstract: Cervically inseminated cryopreserved ram spermatozoa have reduced fertility due to poor mucus-penetrating ability. This effect is ameliorated by the addition of 20% (v/v) seminal plasma (SP) to the phosphate-buffered saline (PBS) thawing medium. The aims of this study were to determine whether the impaired mucus penetration was due to alterations in the sperm motility and, if so, whether these alterations were due to the SP or its viscosity, or to the medium components. To this end, artificial SP medium (ASP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
2
13
2
3
Order By: Relevance
“…The threshold established values for LIN and ALH are less strict than those defined for Merino rams (Mortimer & Maxwell, 1999) in which incubation was performed under different conditions to those that we used to achieve ram sperm capacitation (Grasa et al, 2006;Colás et al, 2008a,b). Likewise, another kinematic parameter defined for human capacitated spermatozoa, Dancemean [(DNCmean = (ALH ⁄ LIN) · 100] (Robertson et al, 1988) was also lower than that reported for ram spermatozoa (Mortimer & Maxwell, 2004). It is worthy to mention that in our study, motility assessment was made on a slide, while in Mortimer & Maxwell (1999) a 30-lm deep chamber was used, which could explain the differences obtained.…”
Section: Discussioncontrasting
confidence: 55%
“…The threshold established values for LIN and ALH are less strict than those defined for Merino rams (Mortimer & Maxwell, 1999) in which incubation was performed under different conditions to those that we used to achieve ram sperm capacitation (Grasa et al, 2006;Colás et al, 2008a,b). Likewise, another kinematic parameter defined for human capacitated spermatozoa, Dancemean [(DNCmean = (ALH ⁄ LIN) · 100] (Robertson et al, 1988) was also lower than that reported for ram spermatozoa (Mortimer & Maxwell, 2004). It is worthy to mention that in our study, motility assessment was made on a slide, while in Mortimer & Maxwell (1999) a 30-lm deep chamber was used, which could explain the differences obtained.…”
Section: Discussioncontrasting
confidence: 55%
“…A avaliação de múltiplas características espermáticas em uma única amostra de sêmen com alto grau de acurácia e repetibilidade pode ser realizada através do sistema automatizado de análise de motilidade (CASA) (Mortimer & Maxwell 2004), que tem a vantagem de diminuir a ocorrência de erros e, por sua objetividade, permitir avaliações adicionais, tais como a velocidade e o tipo de trajetória dos espermatozoides. Contudo, sua grande desvantagem são os altos custos de cada avaliação (Aurich 2005).…”
Section: Discussionunclassified
“…It has been observed that incubation of frozen‐thawed sperm with SP (Dominguez et al, ; Maxwell & Johnson, ; Mortimer & Maxwell, ) or with an isolated SP protein fraction (Barrios, ; Bernardini et al, ; Ledesma et al, ) was able to reverse molecular signals of capacitation such as protein tyrosine phosphorylation. Our study evidenced that the percentage of sperm with CTC non‐capacitated pattern was significantly increased by the addition of SP after EY washing, although no effect was observed on unwashed sperm, suggesting either that decapacitating proteins from SP need direct contact with the sperm PM to reduce cryocapacitation signals or that some components of EY sequestered bioactive SP proteins, such as BSPs (Binder of Sperm Proteins).…”
Section: Discussionmentioning
confidence: 99%